16
$\begingroup$

Let $\Delta$ denote the forward difference operator on a sequence: $$\Delta s_n = s_{n+1} - s_n,$$ and $\Delta^m$ denote the forward difference of the order $m$: $$\Delta^0 s_n = s_n, \quad \Delta^{m+1} s_n = \Delta\left(\Delta^m s_n\right).$$ We say that a sequence $s_n$ is completely monotone iff $$(-1)^m \Delta^{m} s_n > 0,$$ i.e. the sequence $s_n$ itself is positive and decreasing, its first differences $\Delta s_n$ are negative and increasing (that is, decreasing in absolute values), its second differences $\Delta^2 s_n$ are positive and decreasing (like the sequence $s_n$ itself), and so on. So, the sequence of second differences of a completely monotone sequence is also completely monotone (and so is the sequence of its differences of any even order).

Let $a$ be a real number in the interval $1<a<e^{1/e}$. Let ${^n a}$ denote tetration: $${^0 a}=1, \quad {^{(n+1)} a} = a^{\left({^n a}\right)}.$$ The sequence ${^n a}$ is strictly increasing and converges to the limit $${^\infty a} = \lim_{n\to\infty}\left({^n a}\right) = \frac{W(-\ln a)}{-\ln a},$$ where $W(x)$ is the Lambert $W$-function. Let $s_n = {^\infty a} - {^n a}$. It appears that the sequence $s_n$ is completely monotone. How can we prove it?

$\endgroup$
  • $\begingroup$ I would start with analytic solution from the Schröder equations which has an imaginary period, $p=\frac{2\pi i}{\ln\ln(L))};$ L is the fixed point; $L=\frac{W(-\ln a)}{-\ln a}$. This is a formal inverse Schröder function which I will call h; where $\lambda=\ln(L)$, which is the multiplier at the fixed point. $h(\lambda z)= a^{h(z)}$. So the superfunction's properties depend a lot on $h(z)$, and if the odd derivatives of h are postive and the even derivatives are negative, then we can show the superfunction's derivatives have the same property desired by the Op. $\endgroup$ – Sheldon L Oct 30 '16 at 14:57
  • 1
    $\begingroup$ Just a question: The function $f_a(n) = \,^n a$ can be expressed by a type of Dirichlet series $f_a(n) = \,^\infty a -( c_0 + c_1 \lambda_1^n + c_2 \lambda_2^n + ... )$ and the differences by$s_a(n) = ( c_0 + c_1 \lambda_1^n + c_2 \lambda_2^n + ... )$ where the $\lambda_k$ are the eigenvalues of the Carlemanmatrix and $ 0< \lambda_{k+1} <\lambda_k $ and also $ 0< c_{k+1} < c_k$ . Empirically we have only a finitely truncated series - but leave this aside here. Wouldn't the "complete monotonicity" follow from such a structure and its derivatives - so wouldn't a proof for that structure suffice? $\endgroup$ – Gottfried Helms Nov 16 '16 at 6:22
  • $\begingroup$ That older post in the tetration-forum math.eretrandre.org/tetrationforum/showthread.php?tid=249 discusses $f_a(n)$ when its series is created by the Schröder-function-mechanism for the example base $a=\sqrt 2$. Perhaps there is something useful for this question, posibly in the postings of Bo29... who tried to give proofs for some detail (limit). You'll find the writing possibly a bit obfuscated, if this ansatz is interesting anyway I would explain it more in an answerbox here. $\endgroup$ – Gottfried Helms Nov 21 '16 at 10:30
7
+200
$\begingroup$

So from my comments above, $\lambda$ is the multiplier at the fixed point. $a^{L+x}=L+\lambda x + O x^2\;\;\ln_a(L+x) = L +\frac{x}{\lambda} + O x^2 $ $$L= \frac{W(-\ln a)}{-\ln a}\;\;\;\lambda=\ln(L)$$

For the bases in question $1<L<e,\;\;0<\lambda<1$. Then an approximate solution for the superfunction for large values of z is $$S_1(z)=L-\lambda^z=L-e^{z \ln(\ln(L))}$$

$S_1(x)$ is a completely monotonic analytic function at the real axis, where the odd derivatives are all >0, and the even derivatives are all <0, which we will use as the definition of a completely monotonic analytic function. This is because $\ln(\ln(L))<0$ for all bases in question; and we substitute that into the Taylor series for exp(z). $\ln_a(x)$ is also completely monotonic from the Taylor series of $\ln(x)$, for the Op's bases, in the domain $0<x<L$, which is the domain we will use in the iterations below. From that initial $S_1(z)$ estimate, we generate a sequence of better and better estimates, which converges to the Schröder function solution by lemma1 which is described below.

$$S_n(z)=\log_a(S_{n-1}(z+1))$$ We can show that $S_n(x)$ is completely monotonic if $Re(x+1)>S^{-1}_{n-1}(0)>$; by lemma2, which is that the composition of two completely monotonic analytic functions is completely monotonic in the appropriate range. In the limit, $S(x)$ is completely monotonic at the real axis if $Re(x+1)>S^{-1}(0)$

$$S(z) = \lim_{n\to\infty} S_n(z)\;\;\;S(z+1)=a^{S(z)} \;\;\; \lim_{x\to\infty}S(x)=L$$

lemma 1, the sequence of $S_n(z)$ functions; $S(z)$ converges to the Superfunction generated from the Schröder equation. I would prove this by generating error estimates from the Superfunction generated from the formal inverse Schröder equation which is periodic; $p=\frac{2\pi i}{\ln{\lambda}}$ so $S(z)$ can be expressed as an analytic Fourier series $S(z)=L+\sum a_n(-1)^n\lambda^{n z}$ where $a_1=1$ and $a_n$ are the formal inverse Schröder function Taylor series coefficients and $S(z)$ converges if $\Re(z+1)>S^{-1}(0)\;\;$ end lemma 1

Then we shift by a constant to get the desired sexp function. $$\text{sexp}_a(z)=S(z+k)\;\;\;k=S^{-1}(0)+1\;\;\;S(k)=1$$

Finally, $\text{sexp}_a(z)$ is completely monotonic at the real axis if z>-2. Then the sequence $^n a=\text{sexp}_a(n)$ is also a completely monotonic sequence by lemma3 that if an analytic function is completely monotonic over a given range, then a sequence of equally spaced samples of that function in that range is also completely monotonic.

So, if we prove lemma(1,2,3), then we have the Ops result. Lemma1 would come from a good book on complex dynamics, Lennart Carlson's book, would be the place to start, but I have seen it mentioned before. The other two Lemmas should be well known in the theory of monotonic functions. Real valued Schröder superfunction solutions will often be fully monotonic; so presumably this is known.

There is a possible alternative approach to lemma1, that $S(x)$ is completely monotonic. As noted above, the formal superfunction solution can be expressed as a Fourier series: $S(z)=L+\sum a_n(-1)^n\lambda^{n z}$ Then $a_1=1;$ and by observation $a_n(-1)^n<0 \;\forall n$. This sequence leads immediately to a completely monotonic solution for $S(z)$ at the real axis although I haven't tried proving the observation.

$\endgroup$
6
$\begingroup$

This answer is an attempt to explain lemma1. Why is $S_1(z)$ the correct initial approximation in the previous answer, and why does the sequence converge? $$S_1(z)=L-\lambda^z=L-e^{z \ln(\ln(L))}\;\;\;S_n(z)=\log_a(S_{n-1}(z+1))$$

Starting with ideas from the previous answer, along with the definition of the inverse Schröder function, which we will call $h(z)$, where the desired $S(z)$ function follows directly from $h(z)$ as follows: $S(z)=\sum a_n(-1)^n\lambda^{n z}\;\;$ where $a_n$ are the Taylor series coefficients of $h(z)$. We start with the fixed point L from the previous answer. $\ln_a(L+z) = L +\frac{z}{\lambda} + O z^2\; $ and the multiplier at the fixed point is $\lambda$. $$L= \frac{W(-\ln a)}{-\ln a}\;\;\;\lambda=\ln(L) = \ln(a) \cdot L; \;\:1<L<e;\;\;0<\lambda<1$$

$$h(z)=\sum_{n=0}^{\infty}a_n z^n\;\;\;a_0=L;\;a_1=1\;\;\;h(\lambda z) = a^{h(z)}\;\;\;\ln_a(h(\lambda z))= h(z)$$ $$S(z) = h(\lambda^z)\;\;\;S(z+1)=a^{S(z)}\;\;\;\lim_{\Re(z) \to \infty}S(z)=L$$

lemma4: if all of the odd Taylor series coefficients of $h(z)$ at z=0 are positive, and all of the even Taylor series coefficients are negative, then $S(z)$ is fully monotonic, since $0<\lambda<1$, and $\lambda^{nz}=-\exp(n\ln(\lambda) z)$ is fully monotonic for all n, since $\ln(\lambda)$ is a negative number, and $a_n(-1)^n$ is also a negative number, so $S(z)$ is fully monotonic under that case.

There is a formal solution for $h(z)$, as the inverse of the Schröder equation. But alternatively, we start with $h_1(z)=L+z$ and iterate as follows.

$$h_{m+1}(z)=\ln_a(h_m(\lambda z))\;\;\; h(z)=\lim_{m\to\infty}h_m(z)\;\;\;h(z)= \ln_a(h(\lambda z))$$

$$h_2(z)=\ln_a(h_1(z)) =\ln_a(L+\lambda z) $$ $$\ln_a(L+z) =\ln_a(L(1+z/L)) = L + \sum_{n=1}^{\infty}\frac{(-1)^{n+1}z^n}{n \cdot \ln(a) \cdot L^n}$$ $$h_2(z)= \ln_a(L+\lambda z) = L + \sum_{n=1}^{\infty}\frac{(-1)^{n+1} \cdot \lambda \cdot z^n}{n \cdot \ln(a) \cdot L^n} $$ $$h_2(z)= \ln_a(L+\lambda z) = L + \sum_{n=1}^{\infty}\frac{(-1)^{n+1} \cdot z^n}{n \cdot L^{n-1}} \;\;\; a_0=L; a_1=1$$

Notice that $\ln_a(z)$ has all odd Taylor series coefficients positive, and all even Taylor series coefficients negative, just as desired. Notice that $h_2(z)$ has all odd Taylor series coefficients positive, and all even Taylor series coefficients negative, just as desired. Similar to lemma2, the composition $h_3(z)=\ln_a \circ h_2(\lambda z)$ has the same property, so $h_3(z)$ has all odd Taylor series coefficients positive, and all even Taylor series coefficients negative, just as desired. And by induction, the function $h_m(z)$ has all odd Taylor series coefficients positive, and all even Taylor series coefficients negative, just as desired, so this is also true of $h(z)$. lemma5: the $h_m(z)$ sequence converges, which has been shown in the literature of complex dynamics. Also, notice that iterating from $h_{m+1}$ from $h_m$ that $a_0=L$, and $a_1=1$, for the Taylor series of each version of $h_m$. This approach is identical but a little bit more rigorous than the iterations in the previous answer, since it directly shows the stability in iterating $h_n(z)$, which makes proving convergence of lemma5 easier. Let us say the golden values of $a_n$ for the formal inverse Schröder function are $g_n$, and we are doing m iterations to generate $h_m(z)$. Then by observation, $\forall n>2, \;a_n=g_n+O\lambda^{m+n}\;$ after m iterations. Formalizing this error estimate would be a way of showing that the $h_m(z)$ sequence converges to $h(z)$, and that lemma5 is valid.

So if lemma2, lemma4, and lemma5 hold, the conclusion is that $S(z)$ is fully monotonic at the real axis in its range of analyticity, where $\Re(z+1)>S^{-1}(0)$

Finally, as in the previous answer we generate the desired sexp function. $$\text{sexp}_a(z)=S(z+k)\;\;\;k=S^{-1}(0)+1\;\;\;\text{sexp}_a(z)=a^{\text{sexp}(z-1)}$$

$\text{sexp}_a(z)$ is completely monotonic at the real axis if z>-2. Then the sequence $^n a=\text{sexp}_a(n)$ is also a completely monotonic sequence by lemma3 that if an analytic function is completely monotonic over a given range, then a sequence of equally spaced samples of that function in that range is also completely monotonic.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.